2000
DOI: 10.1007/bf02817446
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and characterization of β-galactosidase fromLactobacillus crispatus

Abstract: beta-Galactosidase was isolated from the cell-free extracts of Lactobacillus crispatus strain ATCC 33820 and the effects of temperature, pH, sugars and monovalent and divalent cations on the activity of the enzyme were examined. L. crispatus produced the maximum amount of enzyme when grown in MRS medium containing galactose (as carbon source) at 37 degrees C and pH 6.5 for 2 d, addition of glucose repressing enzyme production. Addition of lactose to the growth medium containing galactose inhibited the enzyme s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
25
0

Year Published

2003
2003
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(29 citation statements)
references
References 19 publications
4
25
0
Order By: Relevance
“…3) and the optimum was found to be 4, 2 and 3 % (w/v), respectively, and a further increase in concentration of all these components did not significantly (p<0.05) affect the β-galactosidase production. The role of carbon source on the induction of β-galactosidase production vary among microorganism and in our previous study, β-galactosidase production by L. plantarum MCC2156 was highest when galactose was used as carbon source (Gobinath and Prapulla 2014) which is in accordance with other reports (Kim and Rajagopal 2000;Laxmi et al 2011). Not only the type of carbon source, but also the concentration of the chosen carbon source plays an important role in β-galactosidase production by microorganisms (Fiedurek and Szczodrak 1994;Inchaurrondo et al Different alphabets above each concentration indicate significant difference (p<0.05) 1998).…”
Section: Resultssupporting
confidence: 91%
“…3) and the optimum was found to be 4, 2 and 3 % (w/v), respectively, and a further increase in concentration of all these components did not significantly (p<0.05) affect the β-galactosidase production. The role of carbon source on the induction of β-galactosidase production vary among microorganism and in our previous study, β-galactosidase production by L. plantarum MCC2156 was highest when galactose was used as carbon source (Gobinath and Prapulla 2014) which is in accordance with other reports (Kim and Rajagopal 2000;Laxmi et al 2011). Not only the type of carbon source, but also the concentration of the chosen carbon source plays an important role in β-galactosidase production by microorganisms (Fiedurek and Szczodrak 1994;Inchaurrondo et al Different alphabets above each concentration indicate significant difference (p<0.05) 1998).…”
Section: Resultssupporting
confidence: 91%
“…Lactose is considered to be the best carbon source to induce maximum b-galactosidase by K. fragiles [35], B. coagulans [36] and B. longum CCRC 15708 [37] whereas in the case of L. crispatus, highest b-galactosidase activity is observed in the presence of galactose [38]. In the present study highest enzyme activity was observed in presence of lactose.…”
Section: Growth Curvesupporting
confidence: 47%
“…There are numerous reports on significant effects of utilized carbon sources of galactosidases [16,49,50]. However, these findings are not universal, and depend greatly on the nature of producer.…”
Section: Optimization Of Carbon Sourcesmentioning
confidence: 99%